2022
DOI: 10.3389/fmars.2022.886775
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Microplastics From the Daugava Estuary to the Open Sea

Abstract: This study considers the transport of microplastics (MPs) from inland waters (rivers and lakes) to coastal waters and then to the open sea. A three-dimensional MP Eulerian tracer model based on the HIROMB-BOOS model (HBM) with wave-induced transport and biofouling process is used. Multilayer two-way nested model grids with 3–0.5–0.25–0.05 nautical mile resolutions are applied to resolve relevant riverine–estuarial–coastal hydrodynamics with a focus on the southern waters in the Gulf of Riga. The major river of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Household microplastics are introduced to the sea without a biofilm shell, which leads to somewhat-enhanced spreading while in their floating stage. High-resolution modeling on the estuary scale has shown that the modeling of biofouling and retention in rivers and estuaries can improve this (Frishfelds et al, 2022). Implementing an advanced biofilm growth model like in Kooi et al (2014) should further advance this.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Household microplastics are introduced to the sea without a biofilm shell, which leads to somewhat-enhanced spreading while in their floating stage. High-resolution modeling on the estuary scale has shown that the modeling of biofouling and retention in rivers and estuaries can improve this (Frishfelds et al, 2022). Implementing an advanced biofilm growth model like in Kooi et al (2014) should further advance this.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The model resolution and the ability to resolve the near coastal zone are important factors in simulating the transport of microplastic pollutants originating from land-based sources. High-resolution model simulations are required to resolve the discharge pattern realistically (Frishfelds et al, 2022). The computational efficiency of the applied 1 HBM ocean circulation and tracer transport model makes it possible to do multiyear simulations with a computationally affordable spatial horizontal resolution of approximately 926 m (≈ 0.5 nmi) in the entire Baltic Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highresolution models are needed to resolve the dynamics in the estuarine-coastal continuum. In the Baltic, key areas were modeled with resolutions up to 90 m (Figure 4) to simulate the transition of microplastics from inland waters to the open sea, while also accounting for retention in rivers/ lakes (Frishfelds et al, 2022). In the Mediterranean, high-resolution (~800 m) models were implemented in four coastal areas (Figure 1; Tsiaras et al, 2022).…”
Section: Marine Plastic Modeling and Assessmentmentioning
confidence: 99%
“…High-resolution domains inside the Baltic Sea model domain. The color map represents a surface concentration of 300 µm microplastic particles (number of particles per m 3 ) on April 15, 2018, within the Daugava River plume after a spring flood (Frishfelds et al, 2022). The model resolution in subregions is 0.5 nm for the Baltic Sea, 0.25 nm for the Gulf of Riga, and 0.05 nm for Latvian inland waters.…”
Section: Marine Plastic Modeling and Assessmentmentioning
confidence: 99%